Multifunctional Smart Military Robot with Visual Inspection Robot - “Warrior Robo" - Sushmitha Deb; Mandara V; Shashank P (International Journal of Computer Sciences and Engineering, 2023)
This research provides a cutting-edge method for remote and border surveillance utilizing a Using the most latest 3G technology, a multipurpose robot is used in military and defence applications. This autonomous car is capable of providing border area surveillance in place of soldiers. The robotic car uses the internet as a communication channel and may be operated manually or autonomously. This multimodal robot is employed in isolated and combat zones to find people, bombs, dangerous chemicals, and fire. Due to their finite range of frequency and restricted control which is manual, wireless security robots are traditionally obsolete. It is operating on one`s own and is managed by infrared and ultrasonic sensors. Cell phones are employed as video cameras by initiating a 3G video calls, and its operation is controlled by DTMF decoders. The robot`s path is changed based on real-time information about its surroundings. The experimental findings of the choice of tilt angle and power consumption of solar panels in automated and its manual modes are also illustrated in this study. Under specific conditions, this robotic vehicle is intended for both reconnaissance and surveillance.